Блочно-модульная биогазгенераторная установка для отходов плодовой древесины - Стручаев, Николай Иванович; Стручаєв, Микола Іванович; Struchaiev, Mykola; Караев, Александр Игнатьевич; Караєв, Олександр Гнатович; Karaiev, Oleksandr; Бондаренко, Лариса Юрьевна; Бондаренко, Лариса Юріївна; Bondarenko, Larysa (ТДАТУ, 2020)
RU: Статья посвящена повышению эффективности использования отходов плодовой древесины, путем создания блочно-модульнной биогазгенераторной установки. Предложена схема расположения элементов блочно-модульнной биогазгенераторной установки для отходов плодовой древесины и методика расчета компактных теплоизолированных ёмкостей для биогазгенератора на примере уменьшения потерь энергии в процессе его выработки, находящегося в цикличном процессе. Получены графические зависимости производительности по биогазу от времени в ёмкости реактора сложной формы. Определено время оптимальной продолжительности одного цикла при различном расположении элементов. UK: Стаття присвячена підвищенню ефективності використання відходів плодової деревини, шляхом створення блочно-модульної біогазгенераторної установки. Запропоновано схему розташування елементів блочно-модульної біогазгенераторної установки для відходів плодової деревини та методика розрахунку компактних теплоізольованих ємностей для біогазгенератора на прикладі зменшення втрат енергії в процесі її циклічного вироблення. Отримано графічні залежності продуктивності по біогазу від часу в ємності реактора складної форми. Визначено час оптимальної тривалості одного циклу при різному розташуванні елементів EN: The article is devoted to increasing the efficiency of using fruit wood waste by creating a modular biogas generator plant, the rate of decrease in biogas productivity, a method is proposed for calculating compact heat-insulated containers for a biogas generator using the example of reducing energy losses during its production, which is in a cyclic process. The layout of the elements of the block-modular biogas-generating plant for fruit wood waste is proposed. To solve the optimization problem, we will depict the biogas yield process: the first stage includes sludge unloading, cleaning and preparation of the reactor for operation, loading a new portion of raw materials and bringing the parameters to the operating mode, the second stage - the optimal mode, includes the reaction to a maximum and some local drop, the third section displays a stable decrease in biogas production , which indicates the need to move to the first stage.Graphical dependences of biogas productivity on time in a reactor of complex shape have been determined. The time of the optimal duration of one cycle with different arrangement of elements is determined. It is proved that for a stable supply of biogas to the system, it is necessary that the sections of the cycles corresponding to the completion of the reaction be overlapped by the sections of the cycles of the biogas generator entering the operating mode.It has been proven that in order to pass the successful certification of fruit products according to the GlobalG.AP standard, producers need to organize the process of processing, transforming renewable resources of horticulture - cut branches of fruit trees according to scientifically sound methods, which should ensure not only the appropriate quality of the energy product, but also a certain energy efficiency process. The proposed method for optimizing the cycle time of a biogas generator can be used in the design of modular biogas generating plants for fruit wood waste.
Keywords: энергосбережение; отходы плодовой древесины; потери энергии; компактные ёмкости сложной формы; блочно-модульнная биогазгенераторная установка